Como as redes fixam crenças: uma análise realista da pós-verdade e suas implicações semiótico-pragmáticas - Baggio, Renan Henrique (2021)
The present work aims to elucidate how networks make it possible to fix beliefs, above all, that are not consistent with reality. Based on the writings of Charles Sanders Peirce (1839-1914), we argue that the dynamics of networks increases confidence in dogmatic beliefs and brings them significantly closer to the scientific method, so that their contents are considered equally reasonable, and the reading of facts is compromised. Therefore, we divided our research into three chapters. In the first chapter, we seek to understand how the fixation of beliefs occurs in each of its methods, namely, tenacity, authority, a priori and scientific. That done, we turn our attention to how the transmission of beliefs by contagion through networks alters the criteria for the infallibility of beliefs, enabling dogmatic and scientific beliefs to reach close degrees of reliability. In the second chapter, we analyze the nature of the real and the fallibilist assumptions for truth. We present the way in which post-truth underlies the dynamics of networks and enables contempt for facts, but it succumbs when faced with a philosophy of a realistic approach whose cornerstone resides in alterity. In the third chapter, we proceed through two distinct but complementary biases. From a semiotic perspective, we analyze the nature of the transmission of beliefs by contagion through networks, especially through the playful action of memes. Using a pragmatist approach, we think about the practical consequences of the fixation of beliefs through networks and its implications in view of an evolutionary philosophy of agapastic nature